IBS connection detection machine / Badrul Amin Baharuddin and Noor Rizallinda Ishak - Baharuddin, Badrul Amin; Ishak, Noor Rizallinda (2024)
Innovation drives progress by pushing boundaries, particularly in the construction industry through Industrialized Building Systems (IBS). Recent advancements in digital technologies, automation, robotics, and Building Information Modeling (BIM) have created new opportunities. Key innovations in IBS include integrating robotics and automation enhancing accuracy, efficiency, and safety, thus increasing IBS adoption in Malaysia. Automation improves manufacturing and assembly processes, minimizing human intervention and improving precision and productivity. Specifically, robotics can automate repetitive tasks, boosting quality control and efficiency. This aligns with Sustainable Development Goal (SDG) No. 9, focusing on industry, innovation, and infrastructure. The development of the IBS Joint Connection Detection Machine aims to address challenges in the construction industry, such as low productivity and reliance on foreign labor. Objectives include identifying issues in precast connections, developing a detection machine using Arduino Uno R3, and demonstrating its market potential. The study focuses on automation in construction, specifically detecting improper precast joint connections. The project ensures the machine's alignment with IBS principles of cost-saving and sustainability, with simulations to demonstrate effectiveness. By addressing industry challenges, this innovation promises to improve productivity and precision in the installation of precast panels.